Alliance Foundation Trial 09: A Randomized, Multicenter, Phase 2 Trial Evaluating Two Sequences of Pembrolizumab and Standard Platinum-Based Chemotherapy in Patients With Metastatic NSCLC - Thomas A. Hensing, MD, MS; Xiaofei Wang, PhD; Thomas E. Stinchcombe, MD; Junheng Gao, MS; Michael V. Knopp, MD, PhD; Mark Watson, MD, PhD; Arkadiusz Z. Dudek, MD, PhD; Stephen L. Graziano, MD; Jyoti D. Patel, MD; Bryan A. Faller, MD; Konstantin H. Dragnev, MD; David Kozono, MD, PhD; et al. (JTO Clinical and Research Reports, 2021)
Introduction: The sequence of chemotherapy and pembrolizumab may affect antitumor immune response and efficacy of immunotherapy. Methods: This multicenter, randomized, phase 2 trial was designed to evaluate the efficacy of two sequences of chemotherapy and pembrolizumab in patients with stage 4 NSCLC. Both arms were considered investigational, and the study used a “pick a winner” design. The primary end point was objective response rate by independent radiologic review after eight cycles (24 wk). Patients were randomized 1:1 to arm A (chemotherapy for four cycles followed by pembrolizumab for four cycles) or arm B (pembrolizumab for four cycles followed by chemotherapy for four cycles). Patients in both arms without disease progression after the initial eight cycles continued pembrolizumab until disease progression, unacceptable toxicity, or a maximum of 2 years. Results: From March 2016 to July 2018, a total of 90 eligible patients were randomized (43 patients to arm A and 47 patients to arm B). The objective response rate at 24 weeks in arms A and B was 39.5 % (95 % confidence interval [CI]: 24.9%–54.1 %) and 40.4 % (95 % CI: 26.4%–54.5 %), respectively (p = 0.93). The progression-free survival in arms A and B was as follows: hazard ratio of B versus A equals to 1.06, 95 % CI: 0.68–1.66, p value equals to 0.84, and median progression-free survival of 5.8 months and 4 months, respectively. The overall survival was as follows: hazard ratio of B versus A equals to 1.04, 95 % CI: 0.63–1.74, p value equals to 0.85, and median overall survival of 15.5 months and 14 months, respectively. Conclusions: Additional evaluation of either sequence in a phase 3 trial is not warranted.